2011
DOI: 10.4155/bio.11.137
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Flow Bioanalysis in Drug Metabolism and Pharmacokinetics

Abstract: Turbulent flow chromatography (TFC) as an analytical technique was introduced in the mid-1990s for online sample processing in bioanalysis. Turbulent flow columns are packed with large particles permitting the use of high mobile phase linear velocities. Solute molecules travel in a uniform concentrated band in which large matrix biomolecules are effectively separated from lower molecular weight analytes by differential mass transfer effects. In addition, the use of various bonded stationary phases enhances sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…However, with this material peak broadening occurred after only a few injections due to saturation of the column by binding of components present in the enzyme preparation, most likely proteins. In literature it has been reported that the so called turbulent flow chromatography is suitable for separating large molecules from low mass analytes [32]. The columns used in this type of chromatography consist of porous particles with sizes that generally range from 30 to 50 m. Operating at high flow rates of the mobile phase of about 4 mL/min for 1 mm internal diameter columns leads to turbulent flows in the column preventing large biomolecules to diffuse into the pores of the stationary phase.…”
Section: Incubation Procedure On-line Solid-phase Extraction and Hplmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with this material peak broadening occurred after only a few injections due to saturation of the column by binding of components present in the enzyme preparation, most likely proteins. In literature it has been reported that the so called turbulent flow chromatography is suitable for separating large molecules from low mass analytes [32]. The columns used in this type of chromatography consist of porous particles with sizes that generally range from 30 to 50 m. Operating at high flow rates of the mobile phase of about 4 mL/min for 1 mm internal diameter columns leads to turbulent flows in the column preventing large biomolecules to diffuse into the pores of the stationary phase.…”
Section: Incubation Procedure On-line Solid-phase Extraction and Hplmentioning
confidence: 99%
“…After 2 min, the valve was automatically switched to position 2 and the analyte was back-flushed off the trap column onto the analytical column with the mobile phase delivered by pump B (acetonitrile/water/phosphoric acid (85%), 77:23:0.1, v/v/v) at a flow rate of 0.4 mL/min. A Waters UV detector 486 was used for detection at 200 nm and system control was performed by Waters Millennium [32] software. The temperature of the autosampler was kept at 10 • C. The analytical column was temperature controlled at 20 • C by a jetstream plus column oven from Waters.…”
Section: On-line Solid-phase Extraction (Spe) and Hplc Analysismentioning
confidence: 99%
“…Quick Elute Mode (Fig. ) is designed for ultra rapid, targeted analysis of small molecules, and was more commonly chosen for early methods using TurboFlow (Rudewicz, ). In the first published method using TurboFlow, Ayrton et al .…”
Section: Turboflow – Modes Of Operationmentioning
confidence: 99%
“…Quick Elute Mode (Fig. 3) is designed for ultra rapid, targeted analysis of small molecules, and was more commonly chosen for early methods using TurboFlow (Rudewicz, 2011). In the first published method using TurboFlow, Ayrton et al wileyonlinelibrary.com/journal/bmc a quantitative, Quick Elute Mode method for a proprietary isoquinoline compound in plasma for toxicokinetic studies.…”
Section: Quick Elute Modementioning
confidence: 99%
“…The recent implementation of automated on-line extraction procedures has allowed fast sample clean-up in bioanalytical applications, and turbulent-flow (or TurboFlow) chromatography (TFC) appears as one of the most interesting ones in this area [102][103][104][105].…”
Section: Turbulent-flow Chromatography (Tfc)mentioning
confidence: 99%